The impact of biopolymers on thermal behavior of meat-biopolymer mixtures-Differential scanning calorimetry (DSC) study - Sarker, Md. Zaidul Islam; Abd Elgadir, Mohammed; Ferdosh, Sahena; Akhtar, Munira; Zainul Abedin, Muhammed; Abdul Hakim, Mohammad; Noda, Takahiro (WFL Publisher, 2013)
Many food ingredients and additives can be used to improve the quality of different food systems. Meat proteins, myofibrillar proteins, sarcoplasmic proteins and collagen, are the main constituents of the structure of meat products. Myofibrillar proteins (about 55% of the total protein content) are composed of several proteins, with myosin and actin being the major ones. Thermal processing is needed for manufacturing processed meat products in general. The alteration in the texture and appearance of meat during cooking is due to denaturation of myofibrillar proteins, sarcoplasmic proteins and collagen. In particular, myosin and actin contribute to the development of desirable gel properties of processed meat products. Biopolymers are the principal category of functional agents that have been used in meat-biopolymer mixtures for many technological purposes, such as improving product texture, controlling viscosity, increasing moisture retention, avoiding oil absorption, and extending overall product quality over time. The presence of biopolymers, such as starch, non-meat protein and hydrocolloids, in meat-biopolymer mixtures could influence the thermal characterization of the system. Differential scanning calorimetry (DSC) has been widely used to analyze the denaturation of meat proteins. Transition temperatures for meat proteins range from 43 to 67°C for myosin subunits, 67 to 69°C for sarcoplasmic proteins and collagen, and 71 to 83°C for actin. The impact of starches, non-meat proteins, and hydrocolloids (carrageenan, flaxseed gum, curdlan and barley β-glucan) on the thermal behavior of meat proteins from different animal species using DSC is reviewed, and the range of functions that biopolymers have in meat-biopolymer mixtures is summarized.